2006
DOI: 10.1080/10408390500295458
|View full text |Cite
|
Sign up to set email alerts
|

Shigellaas a Foodborne Pathogen and Current Methods for Detection in Food

Abstract: Shigella, the causative agent of shigellosis or "bacillary dysentery," has been increasingly involved in foodborne outbreaks. According to the Centers for Disease Control and Prevention's Emerging Infections Program, Foodborne Diseases Active Surveillance Network (FoodNet), Shigella was the third most reported foodborne bacterial pathogen in 2002. Foods are most commonly contaminated with Shigella by an infected food handler who practices poor personal hygiene. Shigella is acid resistant, salt tolerant, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 104 publications
1
66
0
Order By: Relevance
“…One of the striking features of foodborne outbreaks caused by shigella is that in many situations contamination of foods may not have originated pre-harvest in the field (e.g. from fecally contaminated irrigation water) or post-harvest at the processing plant but rather the source can be traced to symptomatic or asymptomatic food handlers [27]. The spread of the pathogen may occur via fingers, flies, or inanimate objects such as utensils and cutting surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…One of the striking features of foodborne outbreaks caused by shigella is that in many situations contamination of foods may not have originated pre-harvest in the field (e.g. from fecally contaminated irrigation water) or post-harvest at the processing plant but rather the source can be traced to symptomatic or asymptomatic food handlers [27]. The spread of the pathogen may occur via fingers, flies, or inanimate objects such as utensils and cutting surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other isolated coliformic Enterobacteriaceae, Shigella sp. was identified even though we did not use any selective methodology [32] to trace it. This observation is of great concern since Shigella even in low doses can cause severe gastrointestinal infection through seafood consumption [33] and it points out the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have concluded that several outbreaks of shigellosis were associated with the consumption of fresh products that are prepared by hand and are served uncooked or raw [22][23][24]. In addition, previous research data indicated that consumption of unhygienic food is the most common contributing factor in shigellosis in underdeveloped and developed nations [25][26][27]. The detection of Shigella species from ready-to-eat salad revealed the inadequate safety and quality of these products.…”
Section: Resultsmentioning
confidence: 99%